The Issues Arising in Connection with the Trade of Precious Metals, Stones and Some Aspects of Legal Regulation in this Field - Adolat Settiyeva Faxriddin qizi (European Science Publishing, 2024)
The article discusses a new sector in the field of precious stones and metals in the Republic of Uzbekistan, as well as an industry considered important from a legal perspective - the activity of extracting precious metals by gold prospectors. The current issues in the field, along with existing practices, are highlighted. Based on the research conducted within this topic, theoretical and scientific recommendations for the future development of the field are provided.
Keywords: precious stones, precious metals, subsoil use, “E-auction”, extraction of precious metals by gold prospectors, geological exploration, illegal extraction of precious metals by individuals.